Protein intake, body composition and athletic performance - Case, Jennifer A. (Kansas State University, 2010)
Background: Mixed Martial Arts (MMA) is a growing sport that places competitors into specific weight classes to level the competition field. Athletes “cut weight” to compete in a weight class lower than their “walk around” weight. Techniques for cutting weight include dehydration, starvation and exercise in hot environments jeopardizing health and performance. Higher-protein diets (HPD) have been shown to improve weight loss by increasing satiety, thermogenesis, decreasing total energy intake, and maintain lean mass during periods of energy deficiency, such as weight loss. Research regarding the impact of HPD on performance is limited and conflicting. Specific Aims: The central hypothesis for this study was: HPD diets will elicit greater weight loss and enhance body composition compare to tradition low-fat diets in non-obese, active individuals. The three specific aims of this study are: 1) examine the effects of HPD on weight loss, 2) evaluate the impact of HPD of athletic performance, and 3) determine the effectiveness of HPD for accelerated weight loss. Methods: Military personnel participating in the Combatives program were recruited. Participants were assigned a HPD (40% CHO, 30% PRO, 30% fat), traditional low-fat, high-carbohydrate diet (65% CHO, 15% PRO, 20% fat), or an ad libitum diet for 12-day to 6-weeks depending on their training program. Fields tests for pre- and post-intervention measures of performance included: vertical jump and leg power index to measure explosive power, 600 meter shuttle run for anaerobic capacity and 1.5 mile run for aerobic capacity. Pre- and post-intervention of weight and body composition were determined using dual energy x-ray absorptiometry. Diet analysis software was used to determine nutrient intakes during the study. SPSS statistical software was used to determine descriptive statistics, paired t-tests, Pearson’s Correlations and one-way ANOVA. Results & Conclusions: Due to the unanticipated high rate of dropout, statistical significance was difficult to determine, however, there was a trend for the HPD to elicit fat-free mass retention and it not negatively impact performance. Discrepancies in energy and nutrient intake made dietary comparison difficult. Future studies with larger samples and greater dietary control are needed to further evaluate the research goals of this study.
Keywords: Sports nutrition; Athletic performance; Higher protein diets; Weight Cutting; Health Sciences, Nutrition (0570)